“The heart and soul of patriotic America”: American conservative women crusading for the “Bricker Amendment” (1953-1957) - Florence Kaczorowski (European Journal of American Studies)
This paper will examine the crusade that a group of conservative women, the Vigilant Women for the Bricker Amendment (VWBA), active in the Republican Party and conservative women’s clubs, carried out to pressure politicians and sway public opinion in favor of the so-called “Bricker Amendment,” devised to limit the treaty-making powers of the President in the 1950s. The VWBA, born out of the efforts of influential anticommunist conservative organizations, successfully promoted anti-statist and anti-internationalist ideas at the local level: in their neighborhood, in women’s clubs, at church or in the local press. A case study of Vigilant Women reveals the prominent role these women played in the formation and activation of a large conservative grassroots network. I will examine the prevalence of the domestic ideology and populist rhetoric in the discourse of VWBA and their allies, and try to demonstrate how resurgent domesticity in the post-WWII period shaped these women’s activism as they engaged primarily in home-based political action.